Psychotic Symptoms Related Anti NMDA Receptor in Ovarian Teratoma - Cecep Sugeng Kristianto (HM Publisher, 2020)
Psychotic symptoms related ovarian teratoma are uncommon but has been well known in previous medical literature. Psychotic problems experienced by patients are often mistaken for psychological causes without organic causes, because commonly patients do not show symptoms associated with teratomas. Diagnosis of teratoma-related psychotic illnesses is often delayed due to the nature of the symptoms, that is leading to delayed treatment and worsen long-term neurological outcomes. Neuropsychiatric symptoms in teratoma can occur if it contains brain tissue inside and antibody anti-NMDA (N-methyl-D-Aspartate) receptor. The occurrence of psychotic symptoms in ovarian teratomas is based on cellular mechanisms. Antibodies bind to the NMDA receptor, which leads to the internalization of the cell surface and the relative state of the NMDA receptor hypofunction. While the impact of specific regions and circuit circuits of anti-NMDA receptor antibodies remains to be explored, the mechanism of anti-NMDA receptor encephalitis strengthens the hypothesis that NMDA receptor hypofunction may have a role in schizophrenia and psychosis.